Industrial applications and opportunities for nondestructive evaluation of structural wood members - C. Beall, Frank (Maderas. Ciencia y Tecnología, 2014)
This paper reviews techniques that can or have been used for determining the key properties of structural wood members, largely softwood lumber and structural panels. For solid wood materials, moisture content, density, and defects are underlying basic properties that must be assessed independently to arrive at structural values. In reconstituted materials, an additional variable, adhesive quality dominates. In addition to reviewing these properties, an assessment is provided for the state of maturity of the relevant technologies.